2021
DOI: 10.3390/v13020175
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Genetic Variability of HHV-8/KSHV among Rural Populations and Kaposi’s Sarcoma Patients in Gabon, Central Africa. Review of the Geographical Distribution of HHV-8 K1 Genotypes in Africa

Abstract: Human herpesvirus 8 (HHV-8) is the etiological agent of all forms of Kaposi’s sarcoma (KS). K1 gene studies have identified five major molecular genotypes with geographical clustering. This study described the epidemiology of HHV-8 and its molecular diversity in Gabon among Bantu and Pygmy adult rural populations and KS patients. Plasma antibodies against latency-associated nuclear antigens (LANA) were searched by indirect immunofluorescence. Buffy coat DNA samples were subjected to polymerase chain reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…Subtypes with the lowest prevalence such as E1, E2 and B1 were from patients living in Spain but born in Cuba, Romania and Mexico, respectively: These subtypes have been described to be widespread in Africa and South/Central America [14]. To our knowledge this is the first case reported in Europe of genotype E. Subtypes E1 and E2 have been previously described in Amerindians [25] and it was also reported in a Cuban study [26]. Consequently, it was consistent that our E1 strain (P95) and those of the Cuban study were found in the same cluster as it has been shown in Fig 1A and 1B.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Subtypes with the lowest prevalence such as E1, E2 and B1 were from patients living in Spain but born in Cuba, Romania and Mexico, respectively: These subtypes have been described to be widespread in Africa and South/Central America [14]. To our knowledge this is the first case reported in Europe of genotype E. Subtypes E1 and E2 have been previously described in Amerindians [25] and it was also reported in a Cuban study [26]. Consequently, it was consistent that our E1 strain (P95) and those of the Cuban study were found in the same cluster as it has been shown in Fig 1A and 1B.…”
Section: Discussionmentioning
confidence: 89%
“…Risk factors associated with KS prevalence and other HHV8-related diseases were age and an immunocompromised status caused by drugs, the host’s genetic factors, viral infections like HIV [ 27 ] and parasite infections like malaria [ 28 ]. Studies from Uganda and Gabon found an association between malaria transmission and HHV-8 prevalence [ 25 ]. In this sense, further studies are needed to stablish this association in ancient malaria endemic areas from the South of Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Second, subclades in subtypes A–E could not be identified in this protocol, which could be of special interest for molecular epidemiology studies carried out in sub‐Saharan Africa where subtype A5 is predominant (Mamimandjiami et al . 2021) and associated with more extensive disease in AIDS patients (Isaacs et al . 2016).…”
Section: Resultsmentioning
confidence: 99%
“…For now, the diversity of KSHV is mainly related to the origin of the patients; subtypes A and C are found worldwide and particularly in North America, Western Europe, the Mediterranean basin and Asia [ 112 , 113 , 114 ]. The variant A5, on the contrary, was first, and is mainly, reported in Africa, as is the subtype B [ 115 , 116 ]. The subtype D is described in the Pacific Island and Taiwan [ 117 ]; the subtype E is in Native Americans in Brazil [ 118 , 119 ]; the subtype F is in a few individuals in Uganda (variant F1) [ 120 ] and, more recently, in Caucasian MSM living in France (variant F2) [ 121 ]; finally, the subtype Z is described in a small cohort of children in Zambia [ 122 ] ( Figure 4 ).…”
Section: Epidemiologymentioning
confidence: 99%